Influence of field size on the physiological and skill demands of small-sided games in junior and senior rugby league players - Gabbett, T. J.; Abernethy, B.; Jenkins, D. G. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate the effect of changes in field size on the physiological and skill demands of small-sided games in elite junior and senior rugby league players. Sixteen elite senior rugby league players ([mean ± SE] age, 23.6 ± 0.5 years) and 16 elite junior rugby league players ([mean ± SE] age, 17.3 ± 0.3 years) participated in this study. On day 1, 2 teams played an 8-minute small-sided game on a small field (10-m width × 40-m length), whereas the remaining 2 teams played the small-sided game on a larger sized field (40-m width × 70-m length). On day 2, the groups were crossed over. Movement was recorded by a global positioning system unit sampling at 5 Hz. Games were filmed to count the number of possessions and the number and quality of disposals. The games played on a larger field resulted in a greater (p < 0.05) total distance covered, and distances covered in moderate, high, and very-high velocity movement intensities. Senior players covered more distance at moderate, high, and very-high intensities, and less distance at low and very-low intensities during small-sided games than junior players. Although increasing field size had no significant influence (p > 0.05) over the duration of recovery periods for junior players, larger field size significantly reduced (p < 0.05) the amount of short-, moderate-, and long-duration recovery periods in senior players. No significant between-group differences (p > 0.05) were detected for games played on a small or large field for the number or quality of skill involvements. These results suggest that increases in field size serve to increase the physiological demands of small-sided games but have minimal influence over the volume or quality of skill executions in elite rugby league players.